THE RELEVANT FACTORS OF EMPLOYEE EFFICIENCY AS A MULTIDIMENSIONAL CONSTRUCTS IN NIGERIAN BANKING SECTOR AFTER CONSOLIDATION - Abdulrahaman, Salmanulfarisi (International Journal For Research In Business, Management And Accounting, 2017)
After consolidation employee productivity was negatively affected by stress, anxiety and fear of losing job. The outcome however, according to Kivuti (2013) among others include; banks are witnessing unnecessary expenses and operating at marginal profit level and at the same time employees found it difficult to meet targets. Using triangulation method the study found that employee efficiency is multi dimensional constructs in Nigerian banking sector. The five factors in descending order are Job Knowledge (14.30%), Job Adaptability (13.96%), and Dependability (13.83%); Interpersonal relations (13.83%) and Compliance (11.73%) indicating that there is more Job Knowledge than other factors in employee efficiency in the banking sector in Nigeria. In total the five factors accounted for 67.06% of the variance in employee efficiency. At 95% confidence level sig. value is statistically significant (.00).The findings of the study lend support to Ha. The study recommended that banks should emphasize on induction courses, training and development and brain storming session for more job knowledge to increase employee efficiency.